1988
DOI: 10.1007/bf01963096
|View full text |Cite
|
Sign up to set email alerts
|

Protein patterns, serotyping and plasmid DNA profiles in the epidemiologic fingerprinting ofPseudomonas aeruginosa

Abstract: The epidemiological typing schemes based on serotyping, antibiotic susceptibility pattern, plasmid DNA profile, and protein patterns determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) were evaluated for their usefulness in typing clinical isolates of Pseudomonas aeruginosa. The serotypability was lower (45%) than reported in the literature (85-95%). The most commonly found serotypes were O:1 (19%), O:11 (25%), O:6 (35%). The electrophoretic analysis of plasmid DNAs showed plasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
(5 reference statements)
2
11
0
Order By: Relevance
“…Whole-cell protein pattern analysis by SDS-PAGE and dendrograms obtained from numerical analysis is one of the techniques used for typing of bacterial species and grouping (Walia et al, 1988). In the present study analysis of whole cell protein from the different isolates using SDS-PAGE indicated that based on banding pattern the isolates can be clubbed into two major groups.…”
Section: T H I S C O P Y I S F O R P E R S O N a L U S E O N L Y -D Imentioning
confidence: 54%
“…Whole-cell protein pattern analysis by SDS-PAGE and dendrograms obtained from numerical analysis is one of the techniques used for typing of bacterial species and grouping (Walia et al, 1988). In the present study analysis of whole cell protein from the different isolates using SDS-PAGE indicated that based on banding pattern the isolates can be clubbed into two major groups.…”
Section: T H I S C O P Y I S F O R P E R S O N a L U S E O N L Y -D Imentioning
confidence: 54%
“…[19] Different electrophoretic methodologies have been employed in the typing of Clostridium species by protein patterns, and it appears to be the most popular general approach. Typeability is extremely high, and in theory all strains can be typed; in practice, well over 95% of isolates can be typed to previously deÞ ned types and any new patterns can be added as new types.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage is that the level of reproducibility reported for the SDS-PAGE technique is extremely high and this is not affected by long-term storage of strains [27].…”
Section: Discussionmentioning
confidence: 99%